Yorùbá Films in Time Perspective: Past, Present, and Future - Ifeoluwa Theophilus Akinsola (Yoruba Studies Review)
This essay (re)views the development of Yoruba films according to the Yoruba traditional worldview about time: a term used synonymously with life, season or period, for it is not linear but cyclical, just as life, it is not straight. Therefore, the present trend in the Yoruba film industry, whereby skilled film producers now have their films premiered at and release to only cinemas where they could be watched legally and piracy is prevented, is seen in this paper as a return to the origin of the development of the Yoruba films. The Yoruba films started in 1976 at the cinema (past), metamorphosed into video mode in the 1990s which is still in place (present) and gradually going back to the cinema and the stage mode (future from now), which was its origin because the Ogunde dramatic tradition: a stage medium, is agreed as Yoruba film precursor.